2012
DOI: 10.1007/s10409-012-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of heterogeneous propellants from particle packing to grain failure using a surface-based cohesive approach

Abstract: In the present work, a computational framework is established for multiscale modeling and analysis of solid propellants. A packing algorithm, considering the ammonium perchlorate (AP) and aluminum (Al) particles as spheres or discs is developed to match the size distribution and volume fraction of solid propellants. A homogenization theory is employed to compute the mean stress and strain of a representative volume element (RVE). Using the mean results, a suitable size of RVE is decided. Without considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The effect of thickness and inhomogeneity of ITZ on the effective mechanical properties are studied for the realistic demand by following numerical examples. The experimental results and theoretical models indicate that inclusion volume fraction and matrix modulus are key factors controlling the effective mechanical properties [21,23]. In Figs.…”
Section: Numerical Proceduresmentioning
confidence: 88%
“…The effect of thickness and inhomogeneity of ITZ on the effective mechanical properties are studied for the realistic demand by following numerical examples. The experimental results and theoretical models indicate that inclusion volume fraction and matrix modulus are key factors controlling the effective mechanical properties [21,23]. In Figs.…”
Section: Numerical Proceduresmentioning
confidence: 88%
“…However, while considering the dewetting phenomenon in composites, those analytical models are limited to capturing the real strain and stress distribution which is of great importance during the analysis. RVE is wildly used to predict the effective properties of the composites accompanied with the FE analysis, especially for solid propellants [23][24][25][26][27]. In the published literature, there are different definitions of it.…”
Section: Preparations Of the Rve Modelmentioning
confidence: 99%
“…They studied the interface debonding process of propellant and its influence on macro mechanical response through finite element calculation. An approximate characterization of the mechanical response of propellant particle/matrix interface by bilinear cohesion model was carried out by Zhi [11]. It was found that the initial modulus and tensile strength of propellant increased with the increase of the filling volume fraction.…”
Section: Introductionmentioning
confidence: 99%